Recent Advances in Histidine Kinase-Targeted Antimicrobial Agents - Chen, Hongtong; Yu, Chengqi; Wu, Han; Li, Guoqing; Li, Congran; Hong, Wei; Yang, Xinyi; Wang, Hao; You, Xuefu (Frontiers in Chemistry, 2022)
The prevalence of antimicrobial-resistant pathogens significantly limited the number of effective antibiotics available clinically, which urgently requires new drug targets to screen, design, and develop novel antibacterial drugs. Two-component system (TCS), which is comprised of a histidine kinase (HK) and a response regulator (RR), is a common mechanism whereby bacteria can sense a range of stimuli and make an appropriate adaptive response. HKs as the sensor part of the bacterial TCS can regulate various processes such as growth, vitality, antibiotic resistance, and virulence, and have been considered as a promising target for antibacterial drugs. In the current review, we highlighted the structural basis and functional importance of bacterial TCS especially HKs as a target in the discovery of new antimicrobials, and summarize the latest research progress of small-molecule HK-inhibitors as potential novel antimicrobial drugs reported in the past decade